Producción de proteínas a partir de la microalga Chlorella vulgaris enriqueciendo el medio de cultivo con fuentes de nitrógeno (2018)
Chlorella vulgaris microalgae protein has a high nutritional value, its production requires optimal culture conditions to reach high yields and allow large-scale production, for which both high cell densities and the accumulation of proteins are required. the cells. It is known that nitrogen is a limiting factor in growth, being used by microalgae in its metabolic processes, mainly in the synthesis of proteins, this research evaluated growth, biomass productivity and protein yield in crops enriched with nitrogen sources organic and inorganic. Cultures were carried out with a previously selected organic and inorganic source, whey and sodium nitrate respectively, at different concentrations with photoperiods of 12h light: 12h dark at 20 ± 1ºC, determining the highest growth rate of the microalga in 0.041 g / L of nitrogen enriched for the organic source and 0.044 g / L for the inorganic source, finding the highest productivity in the crop enriched by the organic source with 0.07828 g / L * d of biomass, keeping a wide difference with the control crop and with the inorganic source, 0.04841 g / L * d and 0.02559 g / L * d respectively.